CisBP-RNA: a web resource for eukaryotic RNA-binding proteins and their motifs - Rosado-Tristani, Diego; Albu, Mihai; Chen, Xiaoting; Sasse, Alexander; Laverty, Kaitlin U; Ray, Debashish; Tam, Cyrus L; Ernst, Kevin; Lawson, Lucinda P; Morris, Quaid D; Hughes, Timothy R; Weirauch, Matthew T (Nucleic acids research, 2025)
RNA-binding proteins (RBPs) are key mediators of post-transcriptional gene regulation, including splicing, transport, stability, and other facets of RNA metabolism. Many RBPs exert their function through sequence-specific protein-RNA interactions. RBP RNA-binding specificity models, or motifs, are thus essential for understanding post-transcriptional gene regulatory mechanisms. Here, we present CisBP-RNA (Catalog of inferred sequence Binding Preferences of RNA-binding proteins), a freely available web-based database that provides centralized access to eukaryotic RBP motif data. A key feature of CisBP-RNA is the availability of both experimentally determined motifs and motifs that are computationally predicted via our homology-based approaches. The current version of CisBP-RNA catalogs >148 000 sequence-specific RBPs across 690 eukaryotic species. Motifs are currently available for >34 000 of these RBPs. Motif data are available for download in a variety of formats for downstream computational analyses. In addition, CisBP-RNA provides user-friendly web-hosted tools to scan for predicted RBP binding sites, predicts motifs for a protein of interest, and compares a motif to motifs contained in the database. The CisBP-RNA database can be accessed through www.cisbp.org/rna/.
Veröffentlicht: 29. Oktober 2025
Gesehen am 08.12.2025